Interpreting the Placeness of Scavenger Children through Dream Houses Images - Andi Karina Deapati; Mohammad Mochsen Sir; I Irfan (Architectural Research Journal, 2022)
Home and neighborhood are sight that are attached to the memory of every child and will provide a different experience for each of them. A child who lives in a city has a different experience of space from one who lives in a village, as well as those who live by the river and those who live on the edge of the railroad tracks. This study aims to trace the meaning of placeness for children in suburbs with weak economic conditions and still living in non-permanent homes. Placeness will be tracked through the resulting image. The method used is observation and interpretation. Observations are done by looking at the condition of the house and the surrounding environment, then giving instructions and facilities for children to draw a house according to their dreams. The drawing process is observed with minimal guidance so that children can be more free, imaginative, and creative in producing drawings. After that, the drawings were collected and asked each child to explain its meaning, the child's explanation was added with a description of the interpretation using a content analysis approach. Research showed that each child draws a dream house that is different from the house they live in, the drawing of the house is made permanent, larger and mostly multi-storey (two floors), there is a river, a swimming pool, with trees and flowers around it and a picture of the sun and clouds in the background. This phenomenon is the condition of the environment that is close to his house, rivers, various luxury two-story housing, swimming pools and the sun and clouds are common objects and are always present every day in children's lives.